2019
DOI: 10.5812/ijcm.85357
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Relationship Between Risk Factors for Cervical Cancer and Knowledge and Attitude of Health Workers Toward Pap Smear in Isfahan and Its Comparison with Chaharmahal and Bakhtiari Province, Iran

Abstract: Background: Cervical cancer is one of the most common cancers in the female reproductive system. Awareness of cervical cancer diagnosis, risk factors and screening can lead to rapid treatment and their well-being. Methods: This cross-sectional study was conducted on 1900 female health workers in Isfahan province and 230 similar women in Chaharmahal and Bakhtiari province. A researcher-made questionnaire was used to collect data about knowledge and attitude. Numerical outcomes were analyzed using ANOVA and line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“… 17 Mohammadi et al reported that the most important reasons for not performing the PS in health workers in Isfahan were lack of problems in the reproductive system, reluctance to take the test, lack of self-care, and awareness. 3 These results have also been mentioned in other studies too. 18 , 19…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“… 17 Mohammadi et al reported that the most important reasons for not performing the PS in health workers in Isfahan were lack of problems in the reproductive system, reluctance to take the test, lack of self-care, and awareness. 3 These results have also been mentioned in other studies too. 18 , 19…”
Section: Discussionsupporting
confidence: 71%
“…As per the GLOBOCAN 2020 report, it is the fourth most frequent cancer in women on a global scale, 1 yet is predicted to rise to the first rank by 2030. 2 Half of all women who die from cancer worldwide have cervical cancer, 3 and most of them (80%-85%) live in low- and middle-income countries. 3 Developing regions will face almost two-third of the cervical cancer cases predicted for 2050.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health service providers in this context include doctors and midwives. 18 In addition, obstacles in cervical cancer management programs include the negative attitudes of service providers due to lack of competence in carrying out screening for cervical cancer, leading to dependencies in providing services. 19 The results of the study show that knowledge is one of the factors that can affect the performance of a midwife in conducting early detection of cervical cancer using the IVA method.…”
Section: Resultsmentioning
confidence: 99%
“…As it is known, the most important risk factors of CC are human papillomavirus (HPV), smoking, weak immune system, low socio‐economic level, malnutrition, early and long‐term oral contraceptive use, early sexual intercourse, sexually transmitted diseases, multiple sexual partners and high number of pregnancies (American Cancer Society, 2020; Cohen et al, 2019; Kashyap et al, 2019; Kaur et al, 2019; Mohammadi et al, 2019; Selçuk & Yanikkerem, 2020).…”
Section: Introductionmentioning
confidence: 99%